2021
DOI: 10.1038/s41467-021-22117-z
|View full text |Cite
|
Sign up to set email alerts
|

Defective metabolic programming impairs early neuronal morphogenesis in neural cultures and an organoid model of Leigh syndrome

Abstract: Leigh syndrome (LS) is a severe manifestation of mitochondrial disease in children and is currently incurable. The lack of effective models hampers our understanding of the mechanisms underlying the neuronal pathology of LS. Using patient-derived induced pluripotent stem cells and CRISPR/Cas9 engineering, we developed a human model of LS caused by mutations in the complex IV assembly gene SURF1. Single-cell RNA-sequencing and multi-omics analysis revealed compromised neuronal morphogenesis in mutant neural cul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 110 publications
4
77
0
Order By: Relevance
“…It was recently demonstrated that hypoxic breathing normalizes a detrimental hyperoxia in brain tissue, while activation of the hypoxia-inducible factor (HIF) is not a crucial factor [95]. A new perspective on LS has recently been opened by the observation that switching from glycolytic metabolism to OXPHOS is critical for early neuronal morphogenesis [96]. Defective metabolic reprogramming due to mutations in OXPHOS complexes is thought to be incompatible with normal brain development and might lead to early termination of pregnancy in more cases than previously known.…”
Section: Leigh Syndrome and The Ndufs4 Ko Mouse Modelmentioning
confidence: 99%
“…It was recently demonstrated that hypoxic breathing normalizes a detrimental hyperoxia in brain tissue, while activation of the hypoxia-inducible factor (HIF) is not a crucial factor [95]. A new perspective on LS has recently been opened by the observation that switching from glycolytic metabolism to OXPHOS is critical for early neuronal morphogenesis [96]. Defective metabolic reprogramming due to mutations in OXPHOS complexes is thought to be incompatible with normal brain development and might lead to early termination of pregnancy in more cases than previously known.…”
Section: Leigh Syndrome and The Ndufs4 Ko Mouse Modelmentioning
confidence: 99%
“…Inability to transition to neuronal oxidative phosphorylation causes apoptosis due to excessive conversion of pyruvate to lactate, and potentially a cell fate shift into GFAP-positive glial cells (Zheng et al, 2016b). Considering our observations that there is a marked deficit in MT-ATP6/PDH mutants to commit and generate neuronal subtypes and an increased signal in astroglial markers, these mutations may be impairing the ability to transition from aerobic glycolysis to OXPHOS as previously described with SURF mutations (Inak et al, 2019, 2021). The preferential switch to a glial fate may be promoted by astrocytes having low expression levels or lower active levels of the PDHα subunit (Bélanger et al, 2011; Halim et al, 2010; Itoh et al, 2003; Laughton et al, 2007).…”
Section: Resultsmentioning
confidence: 51%
“…The availability of animal models and brain tissue from biopsies has provided critical insight into this disease. However, our understanding of the etiology and pathology of complex neurological diseases like LS would benefit from human-derived platforms such as induced pluripotent stem cell-derived models (Inak et al, 2021; Lorenz et al, 2017; Quadrato et al, 2016). The ability to reprogram somatic cells into induced pluripotent stem cells (iPSCs), followed by differentiation into specific lineages has become a useful tool for complex disease modeling (Kelava and Lancaster, 2016; Di Lullo and Kriegstein, 2017; Pașca, 2018; Quadrato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue specific nature of mitochondrial diseases means that mitochondrial function post-differentiation can be distinct to that from the undifferentiated stem cells or original fibroblast line, often greatly exaggerating any underlying defects [ 97 ]. Additionally, detailed transcriptomic and proteomic analyses can elucidate cellular compensation mechanisms and potential target pathways to inform downstream treatment studies [ 98 , 99 ]. Other approaches include microscopic visualization of key cellular features to determine a mutation’s impact on cell structure or function [ 100 ].…”
Section: Disease Modellingmentioning
confidence: 99%